Preoperative Serum Selenium Concentrations and Disease-Specific Survival in Patients With Oral Cancer: A Long-Term Follow-Up Study - Bao, Xiaodan; Chen, Fa; Liu, Fengqiong; Qiu, Yu; Lin, Lisong; Wang, Jing; He, Baochang (Journal of oral and maxillofacial surgery, 2024)
Serum selenium (Se) concentration has been reported to be associated with the incidence of oral cancer. The association between serum Se and long-term survival in oral cancer patients is still unclear. The purpose of this study is to measure the association between serum Se and disease-specific survival (DSS). This was a single-center, prospective cohort study conducted at the First Affiliated Hospital of Fujian Medical University (Fujian Province, China) from September 2011 to December 2018. The inclusion criteria were patients with newly diagnosed primary oral cancer confirmed by histology. The exclusion criteria were patients with recurrent oral cancer or metastatic cancer. The predictor variable is the preoperative serum Se concentration measured using inductively coupled plasma-mass spectrometry. The primary outcome variable is DSS calculated from the date of diagnosis to the date of death due to oral cancer or the end of follow-up, whichever occurred first. The covariates were age, sex, occupation, education level, body mass index, surgery therapy, adjuvant therapy, tumor node metastasis stage, and pathological grading. Kaplan-Meier survival analysis, Cox proportional hazards regression, and restricted cubic spline regression were utilized. P value < .05 was significant. The sample was composed of 235 subjects with a median age of 59 years (ranged from 20 to 80 years) and 142 (60.43%) were male. The median follow-up was 54.90 months (interquartile range: 35.47). Se levels were associated with DSS (unadjusted hazard ratio [HR] = 0.70; 95% confidence interval [CI]: 0.54-0.91) suggesting that higher levels of Se are associated with longer or improved DSS. After adjustment of age, sex, occupation, education level, residence, tumor node metastasis stage, pathological grading, surgery therapy, radiotherapy, and chemotherapy, patients with higher serum Se had a better DSS (aHR = 0.67; 95% CI: 0.49-0.92). Of note, we found that the association between serum Se and DSS was observed only in patients with radiotherapy (aHR = 0.49; 95% CI: 0.33-0.73). And the protective effect of radiotherapy on survival was only observed in patients with higher Se concentrations (aHR = 0.36; 95% CI: 0.20-0.63). Additionally, there was a multiplicative interaction between Se and radiotherapy on the prognosis of oral cancer patients (Pinteraction<0.01). Our findings suggest that a high Se concentration might contribute to better DSS among oral cancer patients, and the effect may partly depend on radiotherapy treatment. Given these findings, additional research should focus on the role of Se in DSS among oral cancer patients and the interaction with radiotherapy.